Knowledge economy: a development perspective - Raghavan, V.P. (2006)
The knowledge economy is an economy of work in progress which requires significant investment in harnessing skills, technology and learning. In a knowledge driven economy, scientific knowledge and information form the major sources for creating value. There should be rapid changes in technology, wherein greater use of information and communication technology help the growth of knowledge intensive industries with increased networking and enhanced social engineering. In the emerging knowledge economy, as much as, if not more than labour and capital, knowledge becomes the basics in creating wealth and improving the quality of life. - Reproduced.
Keywords: Knowledge management